La detención oportuna de hiperbilirrubinemia en el diagnóstico de ictericia en recién nacidos atendidos en el hospital provincial general docente de riobamba, en el período junio- noviembre de 2014. - Vistín Chávez, Carlos Fabián (2015)
This research paper is entitled "timely detection of hyperbilirubinemia in the diagnosis of jaundice in newborns treated at the Provincial General Teaching Hospital in Riobamba in the period June - November 2014" contributes to the determination of the bilirubin levels in newborns before 48 hours of life, to thereby assess whether the child is prone to jaundice and if this is the case for the treating doctor knows differentiate their respective treatment. For this reason it is essential to know that Bilirubin is a bile pigment yellow orange color that results from the breakdown of hemoglobin in red blood cells recycled. Hyperbilirubinemia is the increased level of bilirubin in the blood (normal range 0.3 to 1 mg / dL) and bilirubin builds up in the tissues, especially those with more elastic fibers (palate, conjunctiva). If it is greater than 2 to 2.5 mg / dL, yellowing of the skin and mucosa is observed, and which is known as jaundice. Against this background, the importance of early detection of hyperbilirubinemia in the diagnosis of jaundice in newborn babies receiving care will be demonstrated at the Provincial General Teaching Hospital in Riobamba, in the period from June to November 2014 a population of 150 children were strategically selected to perform respective laboratory tests resulting in 14 possible cases of jaundice diagnosis, signs and symptoms within 24 hours of birth.